Health economics - Sloan, Frank A.; Hsieh, Chee-Ruey (The MIT Press, 2016)
"Health Economics combines economic concepts with empirical evidence to enhance readers' economic understanding of how health care institutions and markets function. The theoretical and empirical approaches draw heavily on the general field of applied microeconomics, but the text moves from the individual and firm level to the market level to a macroeconomic view of the role of health and health care within the economy as a whole. The book takes a global perspective, with description and analysis of institutional features of health sectors in countries around the world."--Provided by publisher.